Experimental Study on Multiple Explosions during the Development and Utilization of Oil Shale Dust - Bo Liu; Yansong Zhang; Yuyuan Zhang; Jinshe Chen; Xiangbao Meng (Shock and Vibration)
Oil shale is a kind of high-combustion heat mineral; in the process of exploitation, storage, and utilization, oil shale dust has the risk of explosion. The explosion characteristics and flame propagation behavior of oil shale dust are worth studying. The difference between the multiple explosion behaviors of oil shale dust was investigated with the use of a 20 L explosive spherical tank and a dust MIE experimental device. The explosion characteristics and microstructure changes of the explosive products in multiple explosions were examined. The experimental results show that the maximum explosion pressure (Pmax) dropped, and simultaneously, the minimum ignition energy (MIE), the explosion time (t), and the maximum rate of pressure rise (dp/dtmax) increased as the explosions continued. Furthermore, the oil shale continued exploding until the third explosion. Some original oil shale dust (OOSD) and explosive residues were analyzed using a scanning electron microscope (SEM) and Fourier transform infrared (FT-IR) spectrometer. The SEM images of the explosive residues indicate a high fragmentation degree and well-developed pore structure during the entire multiexplosion process. Oxygen-containing functional groups, the aliphatic C-H bond, and the aromatic C-H bond in oil shale dust all participated in the oil shale dust explosion process.